An intuitive, abductive argument for a right against mental interference - Douglas, T (Springer, 2024)
Several authors have recently claimed that we each possess a right against interference with our minds. However, it remains unclear how this claim is to be justified. I offer a novel argument in defence of it. The argument is intuitive—appealing centrally to intuitions regarding cases—and abductive—taking the form of an inference to the best explanation; I offer a series of cases involving intuitively wrongful interventions, argue that five somewhat promising attempts to account for the wrongfulness of these interventions leave some of this wrongfulness unexplained, and show that my proposed alternative explanation, which invokes a right against mental interference, can account for this residual wrongfulness.